2021
DOI: 10.47276/lr.92.3.207
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic characteristics of median nerve neuropathy in Hansen’s disease: a case-control study

Abstract: Background and objectives High-resolution ultrasonography (HRUS) has become a vital imaging tool in the management of leprosy. This case-control study analyzed the sonographic data on median nerves in leprosy and healthy controls to identify the features characteristic of leprosy. Methods Newly diagnosed and treatment naïve Hansen's patients of both sexes and aged >16 years were included in the study. The control group included prospectively enrolled healthy subjects. Nerve conduction studies were performed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Our sample consisted of 53 individuals, assessed in detail by a radiologist with experience in the evaluation of peripheral nerves. Although there was no pairing specifically for this study, the data obtained in this group are in accordance with the normality standards used in other studies [ 28 , 30 , 33 ].…”
Section: Methodssupporting
confidence: 84%
See 1 more Smart Citation
“…Our sample consisted of 53 individuals, assessed in detail by a radiologist with experience in the evaluation of peripheral nerves. Although there was no pairing specifically for this study, the data obtained in this group are in accordance with the normality standards used in other studies [ 28 , 30 , 33 ].…”
Section: Methodssupporting
confidence: 84%
“…There were statistically significant differences in ΔUtpt and ΔTtpt values, with higher measurements observed a few centimeters above the tunnel level. Although the median nerve did not differ statistically between the tunnel and pre-tunnel points, thickened nerves were more numerous above the tunnel level [ 33 ]. Previous studies have shown that ΔUtpt possess high specificity for diagnosis of leprosy [ 21 , 22 , 38 ]; however, this is one of the first studies in which this finding was described for the tibial nerve.…”
Section: Discussionmentioning
confidence: 99%
“…The HV group was evaluated in detail by a radiologist with experience in the evaluation of peripheral nerves and, although there was no pairing specifically for this study, the data obtained in this group are in accordance with the normality standards used in other studies [22,[30][31][32]. Considering that the US assessment of peripheral nerves is still a recent technique, we believe that internal standardization is important.…”
Section: Plos Onementioning
confidence: 71%